Validation of Medicinal Leeches (Hirudo medicinalis) as a Non-invasive Blood Sampling Tool for Hematology and Biochemistry Profiling in Mammals - Kvapil, Pavel; Tomášek, Oldřich; Bártová, Eva; Harej, Mojca; Kastelic, Marjan; Primožič, Tit; Kašpárková, Nikola; Račnik, Jožko (Frontiers in Veterinary Science, 2022)
Blood sampling is a challenging procedure in many captive animals. Although manual restraint or anaesthesia are usually possible, they entail intense stress and a high risk of injuries or organ failure. Blood sampling using medicinal leeches (Hirudo medicinalis) represents a promising non invasive alternative to venipuncture; however, leech blood meal was to date used only for qualitative analyses such as genetic or serological screenings. The aim of this study was to evaluate the suitability of the leech blood sampling method for quantification of haematological and biochemical parameters. Medicinal leeches were manually applied on 67 zoo animals of eleven species, and control blood samples were obtained by venipuncture of the jugular vein. The leeches drew up to 20 mL of blood in 20 to 55 min. Although most haematological and biochemical parameters were significantly altered in leech-derived samples, their values showed strong (r = 0.62–0.79; 10/24 parameters) to very strong (r > 0.8; 13/24 parameters) correlations with venipuncture in all blood parameters, except for sodium (r = 0.39). As the parameter alterations and correlations were similar among species, simple cross-species regression formulas were sufficient to correct the alterations, thereby ensuring good repeatability between leeches and venipuncture in most parameters. Our data thus suggest that medicinal leeches can be used as a reliable non invasive and stress-reducing alternative to standard venipuncture, even for quantitative assays. This opens new opportunities for a significant improvement to animal welfare in zoological gardens, conservation programmes, and ecophysiological research, where quantification of blood parameters is often needed.